A FINANCIAL FEASIBILITY STUDY TO DETERMINE THE BEST FUNDING STRUCTURE FOR A TOTAL RENOVATION PROJECT OF THE KAREBOSI FIELD IN MAKASSAR - Asyifa Sufi Setyandri, Nurul
This study aims to determine the best debt-equity combination to fund a PublicPrivate Partnership (PPP) project involving the complete renovation of Karebosi